The lighting transition in Africa: From kerosene to LED and the emerging dry-cell battery problem - Gunther Bensch; Jörg Peters; Maximiliane Sievert (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
Non-electrified people in Africa, still more than 500 million today, have been using kerosene and candles for their lighting purposes for decades. The lighting quality of these sources is low and in particular kerosene usage is associated with harmful soot emissions. Alleviating this grievance has always been a major goal of electrification programs. The present paper shows that in recent years a transition has taken place among the rural non-electrified population in Africa: without any external support from governmental or non-governmental organisations people have replaced kerosene lamps and candles through LED lamps, which are mostly powered by dry-cell batteries. LED lamps are available in rural shops virtually everywhere and provide brighter and cleaner lighting than traditional lamps. The downside of this massive increase of LED usage is a soaring consumption of dry-cell batteries. Because of the toxic content of many dry-cell batteries and since people dispose of discharged batteries inappropriately in latrines or the nature, harmful effects on the local environment are likely. We conclude by suggesting that rapid action is needed to put in place an effective waste management system. – – Menschen ohne Stromzugang in Afrika nutzen seit Jahrzehnten Kerosin und Kerzen zur Beleuchtung. Deren Lichtausbeute ist niedrig und insbesondere die Nutzung von Kerosin ist mit schädlichem Rußausstoß verbunden. Diese Mängel zu beheben war stets ein wesentliches Ziel von Elektrifizierungsprogrammen in der Entwicklungszusammenarbeit. Die vorliegende Arbeit zeigt auf, dass in den letzten Jahren ein Wandel unter der nicht-elektrifizierten Landbevölkerung in Afrika stattgefunden hat: ohne externe Unterstützung von staatlichen oder nichtstaatlichen Organisationen ist es den Menschen gelungen Petroleumlampen und Kerzen durch LED-Lampen zu ersetzen, die größtenteils durch Trockenbatterien angetrieben werden. LED-Lampen sind in ländlichen Geschäften inzwischen praktisch überall erhältlich und bieten helleres und saubereres Licht als traditionelle Beleuchtungsmittel. Die Kehrseite des massiven Anstiegs der LED-Nutzung ist der steigende Verbrauch von Trockenbatterien. Angesichts der giftigen Bestandteile vieler Batterien und einer häufig unsachgemäßen Entsorgung in Latrinen oder in der Natur, sind schädliche Auswirkungen auf die lokale Umwelt und damit auf den Menschen zu erwarten. Wir schließen aus unserer Studie, dass rasches Handeln erforderlich ist, um wirksame Abfallmanagementsysteme zu etablieren.
Keywords: O13; O33; Q53; Q56; 330; electrification; energy access; technology adoption; off-grid energy usage; e-waste